Anais Do XXVIII Simpósio Brasileiro De Informática Na Educação (SBIE 2017) 2017
DOI: 10.5753/cbie.sbie.2017.756
|View full text |Cite
|
Sign up to set email alerts
|

A Math Educacional Computer Game Using Procedural Content Generation

Abstract: Abstract. This paper presents an educational game, MentalMath, with the goal of motivating its users to practice math by solving problems. It uses, besides gamification, procedural content generation, which aims to increase the game's scenarios and problems diversity, tackling some gamification limitations. A preliminary study was conducted with 40 students from a Brazilian school with pre and post written tests, and gameplays data. The results demonstrated that our tool aroused the volunteers' interest in mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
0
11
0
5
Order By: Relevance
“…One major research challenge of PCG for math education is generating math problems at various difficulty levels. Rodrigues et al introduced MentalMath [13], which is an adventure game that requires the players to solve math problems as a final challenge after winning a shooting game at each level. The authors employed a parametric-based method to generate text arithmetic problems based on templates.…”
Section: Related Workmentioning
confidence: 99%
“…One major research challenge of PCG for math education is generating math problems at various difficulty levels. Rodrigues et al introduced MentalMath [13], which is an adventure game that requires the players to solve math problems as a final challenge after winning a shooting game at each level. The authors employed a parametric-based method to generate text arithmetic problems based on templates.…”
Section: Related Workmentioning
confidence: 99%
“…PCG have has applied in EG approaching a varied set of subjects, such as math [Rodrigues et al 2017, Smith et al 2012, Butler et al 2015, Lara et al 2018, computing [Horn et al 2016, Dong and Barnes 2017, Valls-Vargas et al 2017, Dezani et al 2017, resource management [Aslam et al 2017, Luo et al 2017, Grappiolo et al 2011, evolution [Soule et al 2017], therapy [Duval et al 2017], and reading [Hooshyar et al 2018]. In those studies, PCG was mostly used to generate levels or its components (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The exceptions are the cases where the algorithms were analyzed [Soule et al 2017, Smith et al 2012, Valls-Vargas et al 2017, Dong and Barnes 2017 or no user evaluation was performed [Dezani et al 2017]. In contrast, works reporting user-based studies mainly evaluated users' behavior [Butler et al 2015], affective states' changes [Lara et al 2018], learning gains [Hooshyar et al 2018, Rodrigues et al 2017, Horn et al 2016, in-game performance [Aslam et al 2017], opinions [Duval et al 2017], and the proposed approach's performance [Luo et al 2017, Grappiolo et al 2011].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this case, the generated scenario is the environment itself rather than any of the tasks or events taking place within it. Finally, Rodrigues, Bonidia, and Brancher () have developed a math educational computer game using PCG with aim to improve motivation in users to practice math by solving problems. Results of their experiments, similar to previous related works, showed that the proposed game could successfully arouse students' interest.…”
Section: Related Workmentioning
confidence: 99%